Directivity enhancement with improved beamforming for physical layer ultra‐wideband communication by pulse shaping. (27th September 2021) - Sharma, Abhishek; Garg, Amik; Sharma, Sanjay Kumar; Sachan, Vibhav Kumar; Kumar, Parvin
Summary: In this manuscript, a methodology of pulse shape modification is used for the directivity enhancement of ultra‐wideband (UWB) beam formation, to suppress the interference due to co‐existing narrowband communications with UWB signals. We propose that the modified pulse shaping produces more direct beam patterns for the tapped delay line antenna arrangements. These direct beam patterns are obtained for the smaller values of inter‐element spacing. This reduction of inter‐element spacing can provide more space for other development and compact the size of the any UWB antenna unit. Abstract : A new method to minimize the interference between UWB communication and co‐existing narrowband communication is presented. Modified pulse shaping is a possible solution to minimize the interference by controlling not only the PSD of the transmitted signal, but it can also enhance the directivity in a certain direction. The method can provide control over the antenna radiation pattern that can minimize the interference with co‐existing narrowband communications.